Increasing Reading Interest And Ability To Read Explanatory Texts Through The Circ Method In Students - Marlian; Syamsi, Kustam (UNIVERSITAS PAKUAN, 2025)
This study aims to investigate the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in enhancing students’ reading interest and their ability to comprehend explanatory texts. The research employed a quasi-experimental design with pre-test and post-test control groups. The participants were students at the secondary school level, divided into an experimental class that received CIRC-based instruction and a control class that was taught using conventional methods. Data were collected through questionnaires measuring reading interest and reading comprehension tests specifically designed for explanatory texts. The results showed that the CIRC method significantly improved both reading interest and reading comprehension ability compared to the conventional approach. Students in the experimental group demonstrated higher motivation, active engagement in collaborative learning, and improved critical understanding of the text. These findings indicate that the CIRC method is an effective pedagogical strategy to foster reading interest and strengthen reading skills, particularly in the context of explanatory texts. The study contributes to the development of innovative literacy teaching practices and highlights the importance of cooperative learning models in supporting students’ language development